Modified Nonnutrient Agar Plate Culture for the Diagnosis of Strongyloides stercoralis and Hookworm Infections in La-Ngu District, Satun Province, Southern Thailand - Sirima Kitvatanachai; Kanyanan Kritsiriwutthinan; Aree Taylor; Pochong Rhongbutsri (Journal of Parasitology Research)
Due to the low prevalence and light intensity of Strongyloides stercoralis (S. stercoralis, Ss) and hookworm (HW) in Thailand, an increase in the efficacy of detection with the appropriate diagnosis is needed. This cross-sectional survey is aimed at using modified nonnutrient agar plate culture (mNNAPC) to assess the prevalence of S. stercoralis and hookworm infections and to report intestinal parasitic infections in La-Ngu villagers, Satun Province in Southern Thailand. We used wet smear, modified Harada-Mori filter paper culture (mHMFPC), and mNNAPC to investigate 204 villagers (4 villages) between August 2016 and January 2017. The combination of mHMFPC and mNNAPC raised the prevalence of S. stercoralis and hookworm infections among the study population from 3.4% and 1.0% to 6.9% and 2.5%, respectively. There were no significant differences between demographic characteristics and these infections (p<0.05). Three types of protozoal infections, Blastocystis spp. (2.9%), Entamoeba histolytica-like (0.5%), and Giardia duodenalis (0.5%), and 3 species of helminthic infections, S. stercoralis (6.9%) (14 cases), hookworm 2.5%, and Enterobius vermicularis 0.5%, were demonstrated in this area. The mNNAPC showed the highest efficacy in detecting both parasites (Ss 92.9% and HW 80%), whereas the wet smear detected none.